The Effect of Corporate Governance Mechanism, Company Size, Financial Performance, and Environmental Performance On Islamic Social Reporting Disclosure - Annisa Cempaka Devi; Aries Tanno; Fauzan Misra (Ekonomis: Journal of Economics and Business, 2021)
The purpose of this study was to determine the effect of the size of the board of commissioners, the independence of the board of commissioners, the audit committee, managerial ownership, institutional ownership, company size, profitability, and environmental performance on the disclosure of Islamic social reporting in companies listed on the Indonesian Sharia Stock Index. The population of this study consisted of all companies listed on the Indonesian Sharia Stock Index in the period 2014 – 2019. The total sample used in this study was 60 companies. Then, the data were tested using the multiple regression method. The results showed that the size of the board of commissioners, audit committee, firm size, profitability affect the disclosure of Islamic social reporting, while the independent variables of the board of commissioners, managerial ownership, institutional ownership, and environmental performance do not affect the disclosure of Islamic social reporting.